Cyclone Dust Collector Model Filter Design on Incinerator PHC to Reduce the Number of Particles and Air Pollutant Gas Emissions - Hurip Jayadi; Tuhu Pinardi; Beny Suyanto (Alliance oh Health Activists (AloHA), 2021)
Community Health Center organizes inpatient health services, producing infectious, non-infectious waste 0.3 mᶟ / day. Non-infectious waste is burned in an incinerator without a chimney filter, so that the particles, CO, SO2, NOx (emission air pollutants) that are disposed of pollute the ambient air. This research aims to make a cyclone dust collector model of a chimney filter on a public health center incinerator to reduce the amount of air pollutants emitted. Type of experimental research. Implemented at the Maospati Community Health Center, Magetan Environmental Health. This research makes a means of trapping particles and gases with a cyclone dust collector. The independent variable is the depth of the chimney pipe that is inserted into the filter as deep as 0.2m, 0.4m, 0.6m from the starting point of the emission air entering the filter. The dependent variable, the number of particles, gas SO2, NOx, CO. The results of the test tools are presented in the table, analyzed descriptively based on the quality standards of business emissions and / or thermal processing activities. Result:The result, the cyclone dust collector model chimney filter that uses a chimney pipe that is inserted into the filter as deep as 0.2m, 0.4m, 0.6m is able to reduce the amount of particulate emission air pollutants, gas SO2, NOx, CO, but has not been able to reduce it to below the emission air quality standard. The conclusion is that a cyclone dust collector model of a chimney filter on a public health center incinerator can reduce particulate matter, SO2 gas, NOx, and CO emissions. Keywords: incinerator; cyclone dust collector; chimney pipe; particles; pollutant gases